2008
DOI: 10.2337/dc08-1863
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransport Inhibition With Dapagliflozin in Type 2 Diabetes

Abstract: OBJECTIVE -Dapagliflozin, a novel inhibitor of renal sodium-glucose cotransporter 2, allows an insulin-independent approach to improve type 2 diabetes hyperglycemia. In this multiple-dose study we evaluated the safety and efficacy of dapagliflozin in type 2 diabetic patients.RESEARCH DESIGN AND METHODS -Type 2 diabetic patients were randomly assigned to one of five dapagliflozin doses, metformin XR, or placebo for 12 weeks. The primary objective was to compare mean change from baseline in A1C. Other objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
651
8
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(723 citation statements)
references
References 24 publications
46
651
8
13
Order By: Relevance
“…In the short-duration treatment trial with dapagliflozin previously reported, an increase in urinary sodium was initially observed, returning to baseline by day 13 (70). In the pilot study that enrolled 348 patients with type 2 diabetes, it was shown that dapagliflozin displayed a dosage-dependent mild diuretic effect as assessed by daily urine output (71). Unfortunately, urinary sodium was not reported, so we can only speculate whether this diuretic effect was a consequence of glucosuric osmosis or, alternatively, dependent of true natriuresis reflecting the failure of the distal nephron to compensate for the Na ϩ proximal losses.…”
Section: Sglt2 Inhibition: a New Option For The Treatment Of Type 2 Dmentioning
confidence: 88%
See 1 more Smart Citation
“…In the short-duration treatment trial with dapagliflozin previously reported, an increase in urinary sodium was initially observed, returning to baseline by day 13 (70). In the pilot study that enrolled 348 patients with type 2 diabetes, it was shown that dapagliflozin displayed a dosage-dependent mild diuretic effect as assessed by daily urine output (71). Unfortunately, urinary sodium was not reported, so we can only speculate whether this diuretic effect was a consequence of glucosuric osmosis or, alternatively, dependent of true natriuresis reflecting the failure of the distal nephron to compensate for the Na ϩ proximal losses.…”
Section: Sglt2 Inhibition: a New Option For The Treatment Of Type 2 Dmentioning
confidence: 88%
“…When administered for 14 d to drug-naive or metformin-treated patients with type 2 diabetes, dapagliflozin induced a dosage-dependent increase in urinary glucose excretion, reaching a maximum of 70 g/d, and improved fasting blood glucose and glucose tolerance (70). In a more prolonged study, a total of 348 drug-naive patients with type 2 diabetes were randomly assigned to receive 2.5, 5.0, 10.0, 20.0, or 50.0 mg of dapagliflozin; 1.5 g of metformin; or placebo (71). Significant reduction of glycosylated hemoglobin, fasting plasma glucose, and body weight had occurred by the end of the study.…”
Section: Sglt2 Inhibition: a New Option For The Treatment Of Type 2 Dmentioning
confidence: 99%
“…Data were sorted by first author, year of publication, country of the study, design, age range of the participants, total sample size, SGLT2 inhibitor, comparator, number of patients, dosage, and follow‐up duration (Table 1). 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 …”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] A study with dapagliflozin showed a significant reduction in waist circumference, which is consistent with a reduction in fat mass. 19 Studies evaluating body composition suggested that most of the weight loss associated with SGLTi-2 was due to a reduction in visceral or subcutaneous fat.…”
Section: The Kidney As a Treatment Targetmentioning
confidence: 56%